MONSTROUS-FEMALE OF THREE SOUTHEAST ASIAN HORROR MOVIES - Tami, Rosmah; Yulianeta, (Elite : English and Literature Journal, 2025)
This article studies the dynamic changes of two beautiful women into fearful, monstrous females experienced by characters in Indonesian ghost movies such as Sundelbolong, Setan Sumiati, Kuntilanak, Suster Ngesot from Indonesia. This study argues that the changes into ghost pictures represent the reorientation of the earth into a dreadful, hostile nature. The balance of the condition of the narrative describes the harmonic union of the feminine and the masculine in marriage; the break and the loss of equilibrium indicate the grief, rape, and robbery caused by the separation of the feminine from the masculine and the presence of other masculine invaders. The rape and robbery symbolize the invasion and exploitation, and the rage of ghosts signifies the rage of the earth to the invasion and exploitation of unattended land, nature. Yet, they have different structures when narrating the goal of the ghost returning to the world and being forced back to the underworld. These similar structures are influenced by the cultural and political history of the society in which the story belongs. It also unveils how they (the land) deal with colonialization and exploitation.